-29x+6.1=-5(5.8x+2.2)-0.3

Simple and best practice solution for -29x+6.1=-5(5.8x+2.2)-0.3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -29x+6.1=-5(5.8x+2.2)-0.3 equation:


Simplifying
-29x + 6.1 = -5(5.8x + 2.2) + -0.3

Reorder the terms:
6.1 + -29x = -5(5.8x + 2.2) + -0.3

Reorder the terms:
6.1 + -29x = -5(2.2 + 5.8x) + -0.3
6.1 + -29x = (2.2 * -5 + 5.8x * -5) + -0.3
6.1 + -29x = (-11 + -29x) + -0.3

Reorder the terms:
6.1 + -29x = -11 + -0.3 + -29x

Combine like terms: -11 + -0.3 = -11.3
6.1 + -29x = -11.3 + -29x

Add '29x' to each side of the equation.
6.1 + -29x + 29x = -11.3 + -29x + 29x

Combine like terms: -29x + 29x = 0
6.1 + 0 = -11.3 + -29x + 29x
6.1 = -11.3 + -29x + 29x

Combine like terms: -29x + 29x = 0
6.1 = -11.3 + 0
6.1 = -11.3

Solving
6.1 = -11.3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| a+0.05a= | | -45x-1=9(-5x+1)-4 | | -15=5x+10 | | (x+3)(x-4)=-12 | | (2x+3)(6-3x)=0 | | (-8x+8)2=4 | | (50-2x)*(25x+400)=204000 | | 34x+23.4=4(8.5x+4.1)+7 | | 7x+4y=4 | | -10x+17=-2(5x-5)+7 | | lnx+2+lnx+2=6 | | 2x-7=-14 | | log[5]5=x | | x*log[5](x)=18 | | (25k^2)=30 | | F(x+3)=x^2+kx-21 | | x^3+4x^2-19+14=0 | | x*(x-7)=228 | | =sin(9x) | | y=sin(9*x) | | 4[5x+5]=180 | | 3[5x+5]=75 | | 55=5[3x-4] | | -8x^2+16+x^4=0 | | 5[4x-3]=145 | | 236=4[7x+3] | | 7[3x-2]=70 | | 7[3x+3]=126 | | 180=6[4x+2] | | 6[7x-8]=246 | | 5[5x-3]=185 | | 5[3x+7]=125 |

Equations solver categories